2019
DOI: 10.1021/acs.jafc.9b04023
|View full text |Cite
|
Sign up to set email alerts
|

Thermostable Amylosucrase from Calidithermus timidus DSM 17022: Insight into Its Characteristics and Tetrameric Conformation

Abstract: Amylosucrase (EC 2.4.1.4, ASase), a typical carbohydrate-active enzyme, can catalyze 5 types of reactions and recognize more than 50 types of glycosyl acceptors. However, most ASases are unstable even at 50 °C, which limits their practical industrial applications. In this study, an extremely thermostable ASase was discovered from Calidithermus timidus DSM 17022 (CT-ASase) with an optimal activity temperature of 55 °C, half-life of 1.09 h at 70 °C, and melting temperature of 74.47 °C. The recombinant CT-ASase w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
(108 reference statements)
0
5
1
Order By: Relevance
“…Therefore, we have mined a novel ASase from Calidithermus timidus DSM 17022 (CT-ASase). CT-ASase exists as a homotetramer in solution ( 14 ), different from other reported monomeric and dimeric ASase. Although its thermostability still cannot meet industry needs to keep stable above 60 °C, its unique homotetrameric organization may become a key factor to improve its thermostability.…”
contrasting
confidence: 58%
See 2 more Smart Citations
“…Therefore, we have mined a novel ASase from Calidithermus timidus DSM 17022 (CT-ASase). CT-ASase exists as a homotetramer in solution ( 14 ), different from other reported monomeric and dimeric ASase. Although its thermostability still cannot meet industry needs to keep stable above 60 °C, its unique homotetrameric organization may become a key factor to improve its thermostability.…”
contrasting
confidence: 58%
“…Expression and purification of recombinant CT-ASase and its variants were conducted as described in a previous study ( 14 ). The gene encoding CT-ASase and its variants were fused with the sequence encoding a 6× histidine tag at the 3'-terminus and cloned into a pET-22b (+) vector.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermus and Calidithermus bacteria generally grow at medium and high temperature, and their keratinases might have high temperature range and temperature stability, such as MtaKer [11] and aqualysin I [26]. The amylosucrase from Calidithermus timidus has high thermostability with a half-life of 1.09 h at 70 • C [27]. As mentioned above, DgeKer has a long C-terminal extension, as with aqualysin-I [26] and VPR from Vibrio sp.…”
Section: Discussionmentioning
confidence: 99%
“…The draft genome of Calidithermus timidus DSM17022 indicated that the bacterium harbor seven AA, 38 GH, 16 CE sequences 49 . So far, only a GH57-glycogen branching enzyme 50 and GH13 amylosucrase 51 from this bacterium have been analysed in detail. Meiothermus spp.…”
Section: Discussionmentioning
confidence: 99%